Identificação de bacilos Gram positivos aeróbicos isolados de espécimes clínicos em um hospital escola - Maraschin, Mariane de Mello (2007)
In recent years, the gram positive rods have been reported with an increasing frequency as nosocomial pathogens. The recognition those microorganisms as etiological agents of serious infections, such as bacterial sepsis, endocarditis, and catheter infections, have increased, especially in imunocompromised patients. Treatment of these infections has been problematic because the increase in resistance to antibiotics. Graves and sometimes fatal clinical outcomes due to combination of clinical and microbiologic difficulties, including an inappropriate therapy, the difficulty in identifying these organism and failure to recognize their significance, have been reported. Identification of gram positive rods often causes problems. The aim of this study was to propose the serial biochemical probes to identify in comparison with the trade system API Coryne and determine the antimicrobial susceptibility of Gram positive rods isolated from different clinical specimens of patients from the University of Santa Maria Hospital. Between January and December 2005, 50 Gram positive rods strains were isolated. The organisms were identified by conventional biochemical tests and the antimicrobial susceptibility testing was performed by disk-diffusion. Blood-culture 72% (n=36) was the most frequent source. The more prevalent microorganisms were coryneforms 48% (n=24) and Bacillus species, 44% (n=22). Antibiotic susceptibility tests showed good sensibility to vancomycin, linezolid, ciprofloxacin, imipenem and meropenem. However, 6% (n=3) of microorganisms isolated were multi-drug-resistant, included vancomycin, confirmed by the E-test. In our study we demonstrated the efficiency of the suggest battery, with similar efficacy as trade system, as a tool to identification of aerobic gram positive rod isolated from clinical sources.